Pengaruh Spesifikasi Pekerjaan Dan Beban Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Pada Pegawai Pengadilan Negeri Blitar - Bakti, Setia Kurniawan; Arisyahidin, Arisyahidin (Universitas Islam Kadiri, 2024)
The purpose of this research is to determine the mediating effect of job satisfaction in the relationship between jobspecifications and workload on employee performance. The population of this study was 49 employees. Using censussampling, 49 Blitar District Court employees were found as samples. The data collection method uses a questionnaireand analyzes it using the t-test, Ftest, simple and multiple linear regression analysis, and path analysis. The results ofthis study found that job specifications and workload partially or simultaneously had a direct effect on job satisfaction,and job specifications and workload partially or simultaneously had a direct effect on employee performance. Jobsatisfaction has a significant influence on employee performance. Job satisfaction can mediate the relationship betweentransformational leadership and employee performance, which means that the indirect influence of job specifications onemployee performance is greater than the direct influence. Job satisfaction does not mediate the relationship betweenworkload and employee performance, which means that the direct effect of workload on employee performance is greaterthan the indirect effect